Mitigating ageism through intergenerational practices: Lessons from a Portuguese co-constructed local intervention - Sugahara, G.; Oliveira, E. de.; Matos, M. (CIDADES, Comunidades e Territórios, 2026)
The demographic shift's impact on urban utilization, construction, and adaptation has already garnered the attention of city planners. Nevertheless, this relatively 'new interest' is significantly shaped by ageism—a pervasive and negative view of ageing. In 2011, Alcântara, a parish council in Lisbon, was among the city's most aged parishes. Drawing upon a critical gerontology perspective and adopting a co-constructed action research method, this article aims to analyse how intergenerational contact is related to ageism. By triangulating data from surveys, interviews, and field notes collected during an intergenerational project between two social responses — the Senior University and the Family Support Component — in Alcântara, we analyse the outcomes of the intergenerational initiative. We explored the impact, identified the obstacles, and examined situations where ageism was either reproduced or challenged. The participants throughout the project commonly shared perspectives of othering and a narrow interpretation of activeness. The concept of physical decline as an inevitable aspect of ageing was also a recurring theme identified across various phases of the project. This belief had concrete limiting implications on the co-construction of activities Co-construction proved to be a valuable tool, not only for engaging participants in deconstructing ageist stereotypes, but also for highlighting the pervasiveness and negative influence of ageism. We also emphasised the crucial role of the facilitator in maintaining an anti-ageist stance throughout the process.